(The Role of Flavors in Food Industry and Its Development Trend in The Future ) - Agus Sudibyo (Warta Industri Hasil Pertanian, 1991)
Today the food industry is a "flavor era". For many years, it has placed considerable emphasis on the flavor of the "new foods" of the future probably will not differ too greatly from the traditional types of flavors available today. The existing trends portend that future food products will taste much better with flavors more like those of the natural food ingredients. This brief review describe source of flavors, classification of flavoring, The role of flavors in food industry and development trend of flavors in the future.